Concept of criminal offences related to the missequencing of subordination and regulation rules of mutual relations among servicemen (Journal of actual problems of jurisprudence, 2018)
In this article the questions of order of subordination and regulation mutual relations are considered among servicemen, where exposed are concepts of responsibility and prophylaxis of criminal offence in a kind violation of regulation rules of mutual relations between servicemen in default of between them relations of subordination, expressed in causing of beatings, infliction of easy harm to the health or another violence or related to humiliation of honour and dignity or with a mockery above a victim, because in accordance with Constitution Republic of Kazakhstan asserting itself the democratic, society, legal and social state, higher values that be man, his life, right and freedom Key words: In this article the questions of order of subordination and regulation mutual relations are considered among servicemen, where exposed are concepts of responsibility and prophylaxis of criminal offence in a kind violation of regulation rules of.